Expert System Implementation of the Certainty Factor Method for Smartphone Damage Diagnosis - Syahrul Mubarak Abdullah; Andi Syarifuddin; Ahmed Saeed Alghamdi; Hariani Ma'tang Pakka (International Journal Of Electrical Engineering and Inteligent Computing, 2024)
Android smartphone is currently one of the most extensively utilized operating systems. Nevertheless, Android devices are susceptible to issues such as Ic Emmc, Ic Power, software malfunctions, Blank Screen, Hang, complete device malfunction, and boot loop. Prompt intervention is crucial when a smartphone experiences a problem to prevent more harm and safeguard the user. The Certainty Factor (CF) accounts for the inherent uncertainty in an expert's analysis. Expressions such as "uncertain," "highly probable," "likely," "very likely," "almost certain," and "certain" are frequently employed in this context. This study employed a manual questionnaire to assess the efficacy of the expert system in identifying malfunctions in Android devices. All five technicians and all five user respondents expressed significant agreement about the reliability of the expert system in the questionnaire, and the black box test yielded a perfect 100% success rate. Through accuracy testing, using 10 samples of expert analysis data and 10 samples of system data, it was determined that the expert system achieved an 80% accuracy rate in generating diagnostic conclusions based on the tested data.